2000
DOI: 10.1007/s004680000065
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature on mechanical properties of standing lodgepole pine trees

Abstract: To estimate strength parameters of living lodgepole pine stems over a range of temperatures (-16 to +17°C), trees were winched near or past the point of breakage, during which the applied force and deflection of the stem were measured. Trees were 43 years old, 10 m tall, and since the experiments were conducted in the late winter and early spring, when the soil was frozen and the roots were held rigid, the resistance of the stem to deflection could be isolated from the resistances of the root and soil. Static … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 14 publications
(22 reference statements)
1
20
0
Order By: Relevance
“…Given similar dimensions and MOR, branches with high MOE would be stiffer and more brittle. Silins et al (2000) observed increases in both MOE and MOR of the main stem in standing lodgepole pine trees as air temperatures declined below 0°C. Schmidt and Pomeroy (1990) observed a similar increase in stiffness of live subalpine fir (Abies lasiocarpa (Hook.)…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Given similar dimensions and MOR, branches with high MOE would be stiffer and more brittle. Silins et al (2000) observed increases in both MOE and MOR of the main stem in standing lodgepole pine trees as air temperatures declined below 0°C. Schmidt and Pomeroy (1990) observed a similar increase in stiffness of live subalpine fir (Abies lasiocarpa (Hook.)…”
Section: Introductionmentioning
confidence: 78%
“…Consistent with our findings, Schmidt and Pomeroy (1990) observed a linear relationship between force to produce a certain deflection and temperatures less than 0°C on lodgepole pine branches. Silins et al (2000) suggested increased tree or branch stiffness at sub-freezing temperatures may be caused by both a change in the MOE of the wood fibres and changing MOE of ice crystals within the frozen sapwood lumens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil is frozen up to around 50-80 cm below the surface in winter, which may help the roots remain rigid and resistant. Although low temperatures increase the stiffness and strength of trees (Silins et al, 2000), stem breakage was a more significant cause of tree death than was uprooting in forests subjected to strong prevailing winds and heavy snowfall in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Silins et al [9] investigated the effects of temperature on standing lodgepole pines and found that the modulus of elasticity and tensile strength of the trees increased with decreasing temperatures. Umbanhowar [10] and Schmidt and Pomeroy [11] focused there work on the effects of cold on the branches of trees, with similar results.…”
Section: Introductionmentioning
confidence: 99%